2019
DOI: 10.3390/f10090813
|View full text |Cite
|
Sign up to set email alerts
|

Non-Timber Forest Products Collection Affects Education of Children in Forest Proximate Communities in Northeastern Pakistan

Abstract: Non-timber forest products (NTFPs) are crucial in driving the economy of communities living inside or around forests. The scarcity of business and employment opportunities often push the forest proximate communities to tap a range of NTFPs for earning their livelihoods. In many forest-based communities around the world, children are actively involved in NTFPs collection, which is likely to affect the socioeconomic paradigms of these children. We aim to investigate how the NTFP collection venture affects the ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…It was observed that in Neelam district the respondents (56%) were using sickle to extract Non-Timber Forest Products, while in Bagh people (44%) were using hands for the extraction of these plants ( Table 3). [9] Depicted somehow similar results that the people extracting the plants manually usually used them in their daily life but those who extract with the tools were actually selling it.…”
Section: Season and Frequency Of Collectionmentioning
confidence: 79%
See 2 more Smart Citations
“…It was observed that in Neelam district the respondents (56%) were using sickle to extract Non-Timber Forest Products, while in Bagh people (44%) were using hands for the extraction of these plants ( Table 3). [9] Depicted somehow similar results that the people extracting the plants manually usually used them in their daily life but those who extract with the tools were actually selling it.…”
Section: Season and Frequency Of Collectionmentioning
confidence: 79%
“…Often in these communities' children and women are known to be involved in the collection of these plants. These women and children cover extensive distance and endure steep and difficult terrains for the collection of these products and then bring these products in their homes for value addition [9]. Processing and storage are the most important yet neglected aspect of Non-Timber Forest Products business [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1 st stage out of all UCs, 02 UCs (Union Councils) were randomly selected in rural areas of Multan. In the 2 nd stage villages (10) has been selected from 02 UCs. In the 3 rd and final stage of sampling, 10 farmers per village were randomly chosen to make a random sample of 200 respondents.…”
Section: Research Strategy and Samplingmentioning
confidence: 99%
“…Since state land is unable to cope and pace with increasing demand and environmental problems, farmlands remained a feasible solution to grow trees [4,5]. Agroforestry is, therefore, viable alternative to sustain and conserve biodiversity, avert land degradation, provide range of products and services for livelihoods, and mitigate environment in providing distinctive openings for growing biodiversity, averting land degradation, and improving poverty, particularly in developing countries [6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%